The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/09612033221094708
|View full text |Cite
|
Sign up to set email alerts
|

Fibroscan detection of fatty liver and liver fibrosis in patients with systemic lupus erythematosus

Abstract: Objective Although liver dysfunction is not considered the main organ involvement in Systemic Lupus Erythematosus (SLE), the frequency of liver dysfunction or abnormal liver enzyme values may be observed in 50–60% of patients. The aim of this study was to assess fatty liver and liver fibrosis in SLE patients using Fibroscan as well as determine associated factors such as immunosuppressive medications. Methods Sixty SLE patients and 30 healthy controls were included. Patients with HBV, HCV or cirrhosis, maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
3
1
1
Order By: Relevance
“…This, coupled with the younger age of our SLE patients, could partially explain the low prevalence of SLD. Our results are in line with the 23% prevalence reported by Yetginoglu et al in 60 patients with SLE 11 . Of note, in that study, the CAP cutoff point that was used to define steatosis was 238 dB/m rather than the more strongly recommended 275 dB/m, so it is possible that the prevalence in their study could www.nature.com/scientificreports/ even had been overestimated.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This, coupled with the younger age of our SLE patients, could partially explain the low prevalence of SLD. Our results are in line with the 23% prevalence reported by Yetginoglu et al in 60 patients with SLE 11 . Of note, in that study, the CAP cutoff point that was used to define steatosis was 238 dB/m rather than the more strongly recommended 275 dB/m, so it is possible that the prevalence in their study could www.nature.com/scientificreports/ even had been overestimated.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding factors associated with SLD that we found in our study, it is not surprising that metabolic factors such as BMI, waist circumference, and glucose levels were associated with SLD. This is similar to what Yetginoglu et al found in their study 11 , and also to what Zamani et al found in the meta-analysis on rheumatoid arthritis mentioned above, where BMI, rather than methotrexate, was associated with SLD 7 . In contrast, similar to what Yetginoglu et al reported in their study, steroid use was not found to be associated with SLD 11 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[8,16] TE has proven to be an efficient, non-invasive, and consistent method for assessing liver steatosis and fibrosis across various high-risk groups. [17][18][19][20] This is, to our knowledge, the first study that specifically examines the prevalence of TE-confirmed hepatic steatosis and fibrosis in male APs. Our findings show that around 25% of the pilots, who appeared healthy, exhibited steatosis, while approximately 6% had F2 fibrosis or worse.…”
Section: Discussionmentioning
confidence: 97%